Data from: Low fitness at low latitudes: wintering in the tropics increases migratory delays and mortality rates in an arctic-breeding shorebird - Reneerkens, Jeroen; Versluijs, Tom; Piersma, Theunis; Alves, Jose; Boorman, Mark; Corse, Colin; Gilg, Olivier; Hallgrimsson, Gunnar; Lang, Johannes; Loos, Bob; Ntiamoa-Baidu, Yaa; Nuoh, Alfred; et al. (Zenodo, 2020)
1. Evolutionary theories of seasonal migration generally assume that the costs of longer migrations are balanced by benefits at the non-breeding destinations. 2. We tested, and rejected, the null hypothesis of equal survival and timing of spring migration for High Arctic breeding sanderling Calidris alba using six and eight winter destinations between 55° N and 25° S, respectively. 3. Annual apparent survival was considerably lower for adult birds wintering in tropical West-Africa (Mauritania: 0.74 and Ghana: 0.75) than in three European sites (0.84, 0.84 and 0.87) and in subtropical Namibia (0.85). Moreover, compared with adults, second calendar-year sanderlings in the tropics, but not in Europe, often refrained from migrating north during the first possible breeding season. During northward migration, tropical-wintering sanderlings occurred at their final staging site in Iceland 5-15 days later than birds wintering further north or south. Namibia-wintering sanderlings tracked with solar geolocators only staged in West-Africa during southward migration. 4. The low annual survival, the later age of first northward migration and the later passage through Iceland during northward migration of tropical-wintering sanderlings, in addition to the skipping of this area during northward but not southward migration by Namibia-wintering sanderlings, all suggest they face issues during the late non-breeding season in West-Africa. 5. Migrating sanderlings defy long distances but may end up in winter areas with poor fitness prospects. We suggest that ecological conditions in tropical West-Africa make the fuelling prior to northward departure problematic. Data on timing of northward migration of Sanderlings (Calidris alba) through Iceland data_Sanderling.csv R-script used to analyse timing of northward migration of Sanderlings (Calidris alba) through Iceland R script used to analyse timing of northward migration of Sanderlings through Iceland. Explanations can be found in the script and in the accompanying dataset, as well ...